Energy efficiency of wireless sensor network - Lin, Khin Way Way. (2009)
Recent wireless Technology is advancing in energy efficient and enables exciting new applications for wireless devices. These applications requires high performance from the network which constraints on bandwidth and energy. Therefore, to be able to overcome these constraints, we need to implement special protocol architecture rather than the traditional layered approach to obtain the best possible performance. Wireless Sensor Network which consist a large number of sensor nodes is discussed in this project.